Characteristics of tire wear particles generated in a laboratory simulation of tire/road contact conditions. (October 2018) - Park, Inyong; Kim, Hongsuk; Lee, Seokhwan
Abstract: An experimental study of the non-exhaust emission characteristics of tire wear particulate matter (PM) was performed using a tire wear simulator. Building upon previous studies of PM emissions from non-exhaust sources, the total amount of tire wear particles (TWPs) was measured and their morphological and elemental characteristics were investigated. The peak size of TWPs generated at a constant speed of 80 km/h was around 2 µm. Under harsh friction conditions, the mean diameter increased and the size distribution broadened. In addition, the number concentration of ultrafine particles increased significantly. Based on morphological study, we divided TWPs into five categories: sausage-like particles, micron-sized spherical particles, torn debris, ultrafine particles, and aggregates of ultrafine particles. The results of energy dispersive spectroscopy analysis showed that ultrafine particles from tire tread were composed of carbon, silica, and sulfur. Graphical abstract: fx1 Highlights: We investigated the physical characteristics of non-exhaust tire wear particles. Fine and ultrafine particles were measured in the laboratory using a tire simulator. Morphological and elemental analyses can elucidate the particle formation process. The contribution of tire tread wear to airborne PM was estimated in a controlled volume chamber.